Detection, Treatment, and Survival of Pancreatic Cancer Recurrence in the Netherlands: A Nationwide Analysis. Issue 4 (8th April 2022) - Daamen, Lois A.; Groot, Vincent P.; Besselink, Marc G.; Bosscha, Koop; Busch, Olivier R.; Cirkel, Geert A.; van Dam, Ronald M.; Festen, Sebastiaan; Groot Koerkamp, Bas; Haj Mohammad, Nadia; van der Harst, Erwin; de Hingh, Ignace H. J. T.; et al.
Abstract : Objective: To evaluate whether detection of recurrent pancreatic ductal adenocarcinoma (PDAC) in an early, asymptomatic stage increases the number of patients receiving additional treatment, subsequently improving survival. Summary of Background data: International guidelines disagree on the value of standardized postoperative surveillance for early detection and treatment of PDAC recurrence. Methods: A nationwide, observational cohort study was performed including all patients who underwent PDAC resection (2014–2016). Prospective baseline and perioperative data were retrieved from the Dutch Pancreatic Cancer Audit. Data on follow-up, treatment, and survival were collected retrospectively. Overall survival (OS) was evaluated using multivariable Cox regression analysis, before and after propensity-score matching, stratified for patients with symptomatic and asymptomatic recurrence. Results: Eight hundred thirty-six patients with a median follow-up of 37 months (interquartile range 30-48) were analyzed. Of those, 670 patients (80%) developed PDAC recurrence after a median follow-up of 10 months (interquartile range 5–17). Additional treatment was performed in 159/511 patients (31%) with symptomatic recurrence versus 77/159 (48%) asymptomatic patients ( P < 0.001). After propensity-score matching on lymph node ratio, adjuvant therapy, disease-free survival, and recurrence site, additional treatment was independently associated with improved OS for both symptomatic patients [hazard ratio 0.53 (95% confidence interval 0.42–0.67); P < 0.001] and asymptomatic patients [hazard ratio 0.45 (95% confidence interval 0.29–0.70); P < 0.001]. Conclusions: Additional treatment of PDAC recurrence was independently associated with improved OS, with asymptomatic patients having a higher probability to receive recurrence treatment. Therefore, standardized postoperative surveillance aiming to detect PDAC recurrence before the onset of symptoms has the potential to improve survival. This provides a rationale for prospective studies on standardized surveillance after PDAC resection.